KONSTRUKSI PANDANGAN CRITICAL LEGAL THEORY TENTANG THE RULE OF LAW, THE MEANING OF LAW, DAN THE LAW AND SOCIETY - Benediktus Hestu Cipto Handoyo (Arena Hukum, 2018)
AbstractParadigm between the theory of legal positivism and the flow of legal realism shows a difference. The two legal theory paradigms are used as an introduction in discussing Postmodern Legal Theory or called Critical Legal Theory, because the two theories above show the characteristics of Traditional Legal Theory, especially in looking at the rule of law, the meaning of law, and the law and society. The problem in this article is how is the Critical Legal Theory's view of legal concepts specifically related to the rule of law, the meaning of law, and the law and society? Is the statement as stated by Gary Saalman acceptable or not? And does postmodern legal theory do occur in legal reality in Indonesia? This article uses a normative juridical method and a comparison of legal theories through a philosophical approach. The results showed that deconstruction of the old legal theory and included in the postmodern framework in the field of law, although it seemed blindly and "cleared" all the reliability of legal theory, but still contained its own advantages, because with the view of postmodernism itself basic ideas such as philosophy, rationality , and epistemology is questioned radically again.Â  AbstrakParadigma antara Teori hukum positivisme dan aliran Realisme Hukum menunjukkan adanya perbedaan. Kedua paradigma teori hukum tersebut dipergunakan sebagai pendahuluan dalam membahas Teori Hukum Posmodern atau disebut Critical Legal Theory, karena kedua teori di atas menunjukkan ciri-ciri Traditional Legal Theory,Â  khususnya dalam memandang konsep the rule of law, the meaning of law, dan the law and society. Permasalahan dalam artikel ini adalah bagaimana pandangan Critical Legal Theory tentang konsep-konsep hukum khususnya terkait dengan the rule of law, the meaning of law, dan the law and society? Apakah pernyataan sebagaimana dikemukakan Gary Saalman dapat diterima (disetujui) atau tidak? Dan apakah teori hukum posmodern memang terjadi dalam realita hukum di Indonesia?. Artikel ini menggunakan metode yuridis normatif dan perbandingan teori-teori hukum melalui pendekatan filosofis. Hasil penelitian menunjukkan bahwa dekonstruksi terhadap teori hukum lama dan dimasukkan dalam kerangka posmodern di bidang hukum kendati terkesan membabi buta dan â€œmembabatâ€ semua kemapanan teori hukum, namun tetap mengandung kelebihan tersendiri, karena dengan pandangan postmodernisme itu sendiri gagasan-gagasan dasar seperti filsafat, rasionalitas, dan epistimologi dipertanyakan kembali secara radikal.